Meat characteristics of Nellore steers fed whole cottonseed - Costa, Dorival Pereira Borges da; Roça, Roberto de Oliveira [UNESP]; Costa, Quézia Pereira Borges da [UNESP]; Lanna, Dante Pazzanese Duarte; Lima, Erico da Silva [UNESP]; Barros, Wander Miguel de (Sociedade Brasileira de Zootecnia, 2013)
The objective of this study was to evaluate the effect of addition of different levels of cottonseed (0, 14.35, 27.51 and 34.09 kg/100 kg) in the diet of Nellore steers on the meat characteristics. Thirty-six steers (average initial body weight of 333.50 and average age of 20 months) were kept in feedlot stalls for 94 days, each stall with three animals. The experiment was a completely randomized design with four treatments and nine replications. The values of protein, fixed mineral residue, shear force, lipid oxidation, meat color and fat color were similar among the treatments. The increase of the cottonseed levels in the diet reduced the amount of intramuscular fat and increased the moisture content in the meat linearly. Meat aroma and flavor were negatively influenced when cottonseed addition was greater than 27.51 and 34.09 kg/100 kg of the diet, respectively. Cottonseed diet did not modify the concentration of conjugated linoleic acid, saturated fatty acids or total unsaturated fatty acids, but linearly reduced the concentration of monounsaturated fatty acids in the meat.
Keywords: aroma; color; conjugated linoleic acid; flavor; lipid oxidation; shear force